2019
DOI: 10.1029/2018ef001145
|View full text |Cite
|
Sign up to set email alerts
|

Usable Science for Managing the Risks of Sea‐Level Rise

Abstract: Sea-level rise sits at the frontier of usable climate climate change research, because it involves natural and human systems with long lags, irreversible losses, and deep uncertainty. For example, many of the measures to adapt to sea-level rise involve infrastructure and land-use decisions, which can have multigenerational lifetimes and will further influence responses in both natural and human systems. Thus, sea-level science has increasingly grappled with the implications of (1) deep uncertainty in future cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 349 publications
(482 reference statements)
1
74
0
1
Order By: Relevance
“…Complementing AFs with allowances provide a more rounded picture of impact ARTICLE and risk because AFs contain information on the expected future height of ESL events in addition to frequency. However, a complete picture of the flooding risk would also require information on exposure and vulnerability of people and infrastructure 30 , but this is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing AFs with allowances provide a more rounded picture of impact ARTICLE and risk because AFs contain information on the expected future height of ESL events in addition to frequency. However, a complete picture of the flooding risk would also require information on exposure and vulnerability of people and infrastructure 30 , but this is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that accounting for different physics in Antarctica can result in substantially different probabilistic projections of SLR by the end of the century (Jevrejeva et al, 2019;Kopp et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several different plausible estimates of continental‐scale AIS melt exist (e.g., Bamber & Aspinall, ; Edwards et al, ; Deconto & Pollard, ; Golledge et al, ; Levermann et al, ; Little et al, ; Little et al, ; Ritz et al, ), but there is currently not an agreed upon full range of outcomes and likelihoods necessary for risk assessment using a single SLR PDF. Recent modeling of ice sheet behavior, discussed in detail in Oppenheimer et al () and Kopp et al (), demonstrates divergent PDFs and likelihoods of a partial collapse of the AIS from different modeling approaches. An implication of this ambiguity is that the PDF of SLR in the second half of the century remains strongly dependent upon subjective assessment of potential AIS contributions.…”
Section: Frameworkmentioning
confidence: 99%